Prevalence and distribution of type 2 diabetes mellitus in Mexican adult population: a probabilistic survey Prevalencia y distribuición de la diabetes mellitus tipo 2 en población adulta mexicana: una encuesta probabilística - Salvador Villalpando; Vanessa de la Cruz; Rosalba Rojas; Teresa Shamah-Levy; Marco Antonio Ávila; Berenice Gaona; Rosario Rebollar; Lucia Hernández (Instituto Nacional de Salud Pública, 2010)
OBJECTIVE: To describe the prevalence, distribution and degree of control of type 2 diabetes (T2D) in Mexican population. MATERIAL AND METHODS: Subjects were classified as previously diagnosed T2D (PD); or as "finding of the survey" (FS) (glucose >126 mg/dL). Hemoglobin A1c was measured in PD-subjects. RESULTS: The prevalence for PD-T2D was 7.34% (95%CI 6.3, 8.5) and for FS 7.07% (95%CI 6.1, 8.1), summing 14.42%; (7.3 million diabetics). 5.3% of PD-T2D were in good, 38.4% in poor and 56.2% very poor control. Older age (OR=0.96, 95%CI 0.94, 0.97), lower BMI (OR=0.95, 95%CI 0.91, 1.0), were protective for poor control. Affiliation to private services (OR=1.77, 95%CI 0.98, 3.13), larger T2D duration (OR=1.05, 95%CI 1.01, 1.08), and combining oral medication and insulin (OR=16.1, 95%CI 1.61, 161) were riskier. CONCLUSIONS: We found an alarming prevalence of T2D in Mexican population; the majority of PD diabetics are in poor control. Research on the latter is warranted. OBJETIVO: Describir la prevalencia, distribución y grado de control de diabetes tipo 2 (DT2) en población mexicana. MATERIAL Y MÉTODOS: Los sujetos fueron clasificados como "previamente diagnosticados" (PD) o "hallazgos de la encuesta" (FS) (glucosa >126 mg/dL). La hemoglobina A1c se midió en DT2-PD. RESULTADOS: La prevalencia de DT2-PD fue 7.34% (IC95% 6.3, 8.5) y 7.07%.(IC95% 6.1, 8.1) para FS, sumando 14.42% (7.3 millones de diabéticos). Los DT2-PD tenían 5.3% control bueno, 38.4%, malo y 56.2% muy malo. Tener mayor edad (RM=0.96, IC95% 0.95, 0.97) o IMC más bajo (RM=0.95, IC95% 0.91, 1.0) fueron protectores contra mal control. Atenderse en servicios médicos privados (RM=1.77, IC95% 0.98, 3.13), larga duración de DT2 (RM=1.05, IC95% 1.01, 1.08) o recibir hipoglucemiantes más insulina (RM=16.1, IC95% 1.61, 161) fueron de riesgo. CONCLUSIONES: Existe una prevalencia alarmante de DT2 en la población mexicana, la mayoría de los PD-DT2 tenían mal control glicémico. Se necesita más investigación sobre este problema.